Fundamental Understanding of Photocurrent Hysteresis in Perovskite Solar Cells. Issue 13 (8th February 2019) - Liu, Pengyun; Wang, Wei; Liu, Shaomin; Yang, Huagui; Shao, Zongping
Abstract: Organic–inorganic hybrid perovskite solar cells (PSCs) have become a promising candidate in the photovoltaic field due to their high power conversion efficiency and low material cost. However, the development of PSCs is limited by their poor stability under practical conditions in the presence of oxygen, moisture, sunlight, heat, and the current–voltage ( I – V ) hysteresis. In particular, the hysteretic I – V issue casts doubt on the validity of the photovoltaic performance results that are achieved, making it difficult to evaluate the authentic performance of PSCs. This review article focuses on understanding the I – V hysteresis behavior in PSCs and on exploring the possible reasons leading to this hysteresis phenomenon. The various strategies attempted to suppress the I – V hysteresis in PSCs are summarized, and a brief future recommendation is provided. Abstract : One of the problems that restrict the further development of perovskite solar cells (PSCs) is hysteresis, making it difficult to evaluate the reliable performance of PSCs. Recent process regarding the strategies to efficiently reduce hysteresis in PSCs is reviewed. The influential factors and possible reasons are also outlined.